Answer :

12abx2 – (9a2 – 8b2)x – 6ab = 0


12abx2 – 9a2x + 8b2x– 6ab = 0


3ax(4bx – 3a) + 2b(4bx – 3a) = 0


(3ax + 2b)(4bx – 3a) = 0


So, we have


3ax + 2b = 0 or 4bx – 3a = 0



Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Find the roots ofKC Sinha - Mathematics

Find the roots ofKC Sinha - Mathematics

4x2KC Sinha - Mathematics

Find the roots ofKC Sinha - Mathematics

36x2KC Sinha - Mathematics